Redox-Switchable New Phthalocyanines Containing Hydrazono-Thiazole-Carboxylate Fragments: Synthesis, Electrochemical, Spectroelectrochemical and Electrocolorimetric Investigation - ÖZKAYA, ALİ RIZA (SPRINGER/PLENUM PUBLISHERS, 2017)
New phthalonitrile compound with Schiff base, carbothioamide and thiazole moieties as substituents and its corresponding metal-free and metallophthalocyanines (Zn(II), Ni(II), Co(II), and Cu(II)) were synthesized and characterized for the first time. The solubilities of these novel phthalocyanines were high in organic solvents. The redox properties of the compounds have been researched by cyclic voltammetry, square wave voltammetry, controlled-potential coulometry and in situ spectroelectrochemistry in dimethylsulfoxide. The compounds displayed metal and/or phthalocyanine ring-based, generally reversible or quasi-reversible reduction and oxidation processes. The effect of aggregation on the redox behavior of these complexes was also discussed. In general, decreased intensity and broadening in the main Q absorption band and the appearance of a new blue-shifted band confirmed the presence of H-type aggregates in the solutions of the complexes 4, 6 and 8 in DMSO/TBAP. The color changes associated with the redox processes and electrogenerated anionic and cationic redox species were also recorded with in situ electrocolorimetric measurements. In situ UV-vis spectral and associated color changes monitored during the reduction processes of the complexes suggested their applicability in the fields of the electrochemical technologies.
Keywords: Phthalocyanine; Thiazole; Synthesis; Electrochemistry; Spectroelectrochemistry; HETERO-DINUCLEAR PHTHALOCYANINES; MICROWAVE-ASSISTED SYNTHESIS; BALL-TYPE PHTHALOCYANINES; SUBSTITUTED METAL-FREE; GAS-SENSING PROPERTIES; STRUCTURAL-CHARACTERIZATION; METALLOPHTHALOCYANINES; PHOTOPHYSICS; DERIVATIVES; REDUCTION